ROUTING AMBULANCES TO DESIGNATED CENTERS INCREASES ACCESS TO STROKE CENTER CARE AND ENROLLMENT IN PREHOSPITAL RESEARCH - Sanossian, Nerses (Stroke, 2015)
BACKGROUND AND PURPOSE: Emergency Medical Services (EMS) routing of acute stroke patients to designated centers may increase the proportion of patients receiving care at facilities meeting national standards and augment recruitment for prehospital stroke research. METHODS: We analyzed consecutive patients enrolled within 2 hours of symptom onset in a prehospital stroke trial, before and after regional Los Angeles County Emergency Medical Services (EMS) implementation of preferentially routing acute stroke patients to Approved Stroke Centers (ASCs). From January 2005 to mid-November 2009, patients were transported to the nearest Emergency Department, while from mid-November 2009 to December 2012 patients were preferentially transported to first 9, and eventually 29, ASCs. RESULTS: There were 863 subjects enrolled before and 764 after EMS preferential routing, with implementation leading to an increase in the proportion cared for at an ASC from 10% to 91% (P<0.0001), with a slight decrease in paramedic on-scene to Emergency Department arrival time (34.5 minutes [SD 9.1] vs. 33.5 [SD 10.3], p=0.045). The effects of routing were immediate and included an increase in of proportion receiving ASC care (from 17% to 88%, p<0.001) and a greater number of enrolments (18.6% increase) when comparing 12 months before and after regional stroke system implementation. CONCLUSIONS: The establishment of a regionalized EMS system of acute stroke care dramatically increased the proportion of acute stroke patients cared for at ASCs, from 1 in 10 to more than 9 in 10, with no clinically significant increase in prehospital care times, and enhanced recruitment of patients into a prehospital treatment trial.